SALOMATLIKNI ShAKLLANTIRISh VA QOʻLLAB-QUVVATLAShGA ILMIY YONDAShUV - Mamutov, P.J.; Bobojonov, N.M. (SCIENCE and SOCIETY, 2025)
The article discusses the role of a healthy lifestyle (HL) and wellness physical culture (WPC) as key elements in disease prevention, improving quality of life, and promoting active longevity. Modern scientific studies on the significance of physical exercise, balanced nutrition, maintaining psycho-emotional health, and avoiding harmful habits within the HL system are analyzed. The article provides recommendations for integrating principles of physical activity into daily life and examines the prospects of applying wellness physical culture in educational and professional institutions.